Relationship Between Intellectual Capital and University Social Responsibility in Institutional Strengthening of Universities - Alejandro Ticona-Machaca; Dominga M. Cano-Ccoa; Félix H. Gutiérrez-Castillo; Rosalin M. Marín-Cahuana; Marisol G. Zirena-Cano; Litzbel Charaja-Fernandez; Shirley F. Simbrón-Espejo; Rafael A. Anibal-Rivero; Mélida S. Rivero-Lazo; Rolando Oscco-Solorzano (Emerging Science Journal, 2025)
Universities face global challenges that require the integration of intellectual capital management and social responsibility. This study aims to analyze how the articulation between intellectual capital and social responsibility contributes to institutional strengthening in universities. A mixed-method approach was applied, combining bibliometric analysis and systematic literature review following the PRISMA protocol, covering 62 relevant studies from 2019 to 2024. Academic databases, lexicometric techniques, and technological tools were used to ensure methodological rigor and thematic coherence. The bibliometric analysis shows that 96.77% of studies were concentrated mainly in the field of Sustainability, led by universities in the global North with multidisciplinary approaches. The findings reveal that intellectual capital management and university social responsibility reinforce academic quality, stimulate innovation, and foster social commitment, thereby significantly contributing to institutional strengthening. As a novelty, the study highlights that the articulation of these dimensions drives sustainable development, promotes ethical organizational cultures, and strengthens collaborative networks. It also suggests the need for coherent public policies to ensure a lasting impact on universities and society. This comprehensive perspective offers new insights for higher education institutions seeking to integrate these elements strategically to address global challenges and improve their contribution to sustainable development.